Integrating architectural heritage for urban revitalization / Zalina Samadi - Samadi, Zalina (2005)
The heritage awareness heightened in built heritage development in the millennium age and the research acts as personal reaction towards the issue. The design intent of this study is to unfold the treasure shop houses heritage in relation to the urban revitalization in the historical city of Taiping, Perak, Malaysia. The focus was on the shop houses which were found as the most in danger built heritage from demolition, deterioration and development pressure. The scope of study included three main research questions. Firstly, the research drive was to find the row shop houses and road for establishment of heritage area. Secondly, was to integrate architectural heritage as the antique existing treasure for urban revitalization. Thirdly, was to find the suitable design guidelines for the property conservation and revitalization .The methodology involved two main research activities: obtrusive methods and unobtrusive methods. Personal interview and survey research with focus group and public were the obtrusive methods. The unobtrusive method involved two activities: content analysis and direct observation. The research found the heritage vision weaknesses on the definition, strategies, internal support, knowledge, awareness and perception amongst the society. Individual heritage definitions and fast profit interests in the role players found as more dominant than the social benefits. The heritage management that covers technical expertise knowledge and application in heritage tourism were new ideas in Malaysia. Therefore, a guide for heritage conservation is an approach to establish the heritage area in regenerating the historical city. In the dynamic building industry, it is the role of designers to reinterpret the conservation of the past heritage while constructing for present and future heritage for more idealistic tools towards sustainable and quality urban environment.